Proceedings of the 2014 ACM SIGSAC Conference on Computer and Communications Security 2014
DOI: 10.1145/2660267.2660347
|View full text |Cite
|
Sign up to set email alerts
|

The Web Never Forgets

Abstract: We present the first large-scale studies of three advanced web tracking mechanisms -canvas fingerprinting, evercookies and use of "cookie syncing" in conjunction with evercookies. Canvas fingerprinting, a recently developed form of browser fingerprinting, has not previously been reported in the wild; our results show that over 5% of the top 100,000 websites employ it. We then present the first automated study of evercookies and respawning and the discovery of a new evercookie vector, IndexedDB. Turning to cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 344 publications
(110 citation statements)
references
References 22 publications
2
102
0
6
Order By: Relevance
“…First, while prior work has largely focused on creating taxonomies of the types of dark patterns either based on anecdotal data [31,32] or data collected from users' submissions [38,48], we provide large-scale evidence documenting the presence and prevalence of dark patterns in the wild. Automated measurements of this kind have proven useful in discovering various privacy and security issues on the web-including third-party tracking [25,40] and detecting vulnerabilities of remote third-party JavaScript libraries [68]-by documenting how and on which websites these issues manifest, thus enabling practical solutions to counter them. Second, we expand on the insight offered by prior work about how dark patterns affect users.…”
Section: Comparison To Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…First, while prior work has largely focused on creating taxonomies of the types of dark patterns either based on anecdotal data [31,32] or data collected from users' submissions [38,48], we provide large-scale evidence documenting the presence and prevalence of dark patterns in the wild. Automated measurements of this kind have proven useful in discovering various privacy and security issues on the web-including third-party tracking [25,40] and detecting vulnerabilities of remote third-party JavaScript libraries [68]-by documenting how and on which websites these issues manifest, thus enabling practical solutions to counter them. Second, we expand on the insight offered by prior work about how dark patterns affect users.…”
Section: Comparison To Prior Workmentioning
confidence: 99%
“…In this paper, we present an automated approach that enables experts to identify dark patterns at scale on the web. Our approach relies on (1) a web crawler, built on top of OpenWPM [25,40]-a web privacy measurement platform-to simulate a user browsing experience and identify user interface elements; (2) text clustering to extract all user interface designs from the resulting data; and (3) inspecting the resulting clusters for instances of dark patterns. We also develop a taxonomy so that researchers can share descriptive and comparative terminology to explain how dark patterns subvert user decision-making and lead to harm.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Acar et al performed a large-scale study of canvas fingerprinting in "The Web Never Forgets" [68]. They found that scripts utilize the techniques outlined by Mowery and Shacham and notably, they take advantage of the fallback font mechanism of modern browsers to generate even more differences between devices.…”
Section: Canvas Javascriptmentioning
confidence: 99%
“…In 2014, Acar et al performed the "The Web Never Forgets" study [68], where they measured adoption of canvas fingerprinting on homepages of 100,000 Alexa websites. They instrumented the browser to intercept calls and returns to Canvas related methods, and tried to remove false positives by a set of rules (more details in Section 3.1 of [68]). They found 5542 sites out of 100,000 performing Canvas fingerprinting.…”
Section: Adoption Of Fingerprinting On the Webmentioning
confidence: 99%
See 1 more Smart Citation